HOUSE PRICE CHANGES AND ISLAMIC BANK STABILITY: EVIDENCE FROM MALAYSIA - Hui Kok, Shiau; Ismail, Normaz Wana (Journal of Islamic Monetary Economics and Finance, 2019)
In this paper, we examine the relationship between house price and Islamic bankstability in Malaysia. In particular, in relating to Islamic bank stability to Malaysianhouse price changes, we evaluate the nature of the relationship from the perspectiveof nonlinearities. The Autoregressive Distributed Lag (ARDL) model is applied to asample that consists of 9 Islamic banks in Malaysia for the period of 2000-2016. Ourresults indicate that there is an inverted U-shaped relationship between house priceand Islamic bank stability in the long run. Meanwhile, the relationship is insignificantin the short-run. To put it differently, initially, the higher house prices, the more stablethe bank. Then, the impact of house prices on bank stability becomes negative whenhouse prices surpass the threshold point. As far as the bank-specific characteristicsare concerned, the cost to income ratio is found to significantly and negatively relatedto the bank stability. Such a result has policy implications in which it is crucial forachieving balance in the housing market, and efficiently managing the cost is equallyimportant to ensure Islamic bank soundness.